DNA methyltransferase activity in the basolateral amygdala is critical for reconsolidation of a heroin reward memory - Qian, Shuyi; Shi, Cuijie; Huang, Shihao; Yang, Chang; Luo, Yixiao (Frontiers in Molecular Neuroscience, 2022)
Drug addiction is the aberrant learning form that results in recurrent cravings triggered by associated stimuli (drug-related context or cues). Pharmacology or behavior treatment that disrupts reconsolidation can effectively attenuates drug-seeking in addicts. Also, reconsolidation of fear and cocaine memory has been investigated in relation to epigenetic mechanisms regulated by DNA methyltransferase (DNMT). In the present study, we tested the effects of DNMT on reconsolidation of heroin memory. We trained male Sprague Dawley (SD) rats to acquire heroin intravenously by nosepoke for 10 days in a heroin self-administration model. The light/tone conditioned stimulus (CS) was performed with every infusion. Following the 10-day self-administration session, rats received nosepoke extinction session for 9 days and then were subjected to cue-induced retrieval and subsequent cue-induced, heroin-priming-induced reinstatement tests or spontaneous recovery test to assess the heroin-seeking behavior. Bilaterally infusion of the 5-azacytidine (5-AZA, 1 u g per side) to inhibit DNMT into the basolateral amygdala (BLA) immediately after reactivation decreased subsequent cue-induced and heroin-priming-induced reinstatement of heroin-seeking behavior. Conversely, injecting 5-AZA intra-BLA with 6 hours delay after retrieval or injecting 5-AZA with no retrieval did not alter subsequent cue-induced and heroin-priming-induced reinstatement of heroin-seeking behavior. These findings demonstrate that inhibiting the activity of DNMT in BLA disrupts reconsolidation of heroin-associated memory.